Vorapaxar for HIV-associated inflammation and coagulopathy (ADVICE): a randomised, double-blind, placebo-controlled trial. Issue 10 (October 2018) - ,; Kent, Stephen J; Hough, Sally; Kelleher, Anthony D; Law, Matthew G; Hutchinson, Jolie; Catalfamo, Marta; van Bockel, David; Lane, Cliff; Baker, Jason V; Emery, Sean
Summary: Background: Increased D-dimer concentrations are associated with poor cardiovascular and other clinical outcomes in people with treated HIV infection. Proteinase activated receptor-1 (PAR-1) is activated by thrombin and overexpressed by immune cells from HIV-infected people. We aimed to study the efficacy of vorapaxar, a licensed inhibitor of PAR-1, in reducing HIV-associated hypercoagulation and inflammation. Methods: This was a multicentre, double-blind, randomised, placebo-controlled trial done in seven hospital clinics in Australia and the USA. Eligible participants were HIV-infected, aviraemic, were receiving stable antiretroviral therapy, and had D-dimer concentrations greater than 200 ng/mL. We randomly assigned participants (1:1) using computer-generated block lists of size two to receive vorapaxar (2·5 mg orally daily) or matched placebo for 12 weeks. Participants were reviewed and had a blood sample taken at weeks 1, 4, 8, and 12 during treatment, and at a final visit at week 18. The primary endpoint was treatment group difference in changes from baseline D-dimer concentrations after 8–12 weeks of treatment, and was assessed in the modified intention-to-treat population (participants who had at least one dose of study drug or one follow-up visit). This trial is registered withClinicalTrials.gov, numberNCT02394730, and is closed to new participants. Findings: Between Oct 21, 2015, and July 14, 2017, 65 eligible patients were randomly assigned to the placebo group (n=31) or vorapaxar group (n=34). One patient from the vorapaxar group did not receive any study drug, and the modified intention-to-treat population was comprised of 33 patients. D-dimer concentrations after 8–12 weeks of treatment did not differ significantly between groups (difference −0·02 log10 ng/mL, 95% CI −0·10 to 0·05; p=0·56). Vorapaxar treatment was safe and well tolerated in this cohort. There were 161 adverse events (n=84 in the placebo group and n=77 in the vorapaxar group), and five protocol-defined serious adverse events that required hospital admission for more than 24 h (n=2 in the placebo group and n=3 in the vorapaxar group). One patient ceased taking vorapaxar because of an adverse event. There were 25 bleeding events, 23 of which were mild, one was moderate, and one was severe. Interpretation: Vorapaxar had no effect on D-dimer concentrations in HIV-infected patients receiving stable antiretroviral therapy but at risk of poor outcomes. Alternative approaches are needed to reduce hypercoagulation, inflammation, and adverse long-term outcomes in patients with treated HIV infection. Funding: Australian National Health and Medical Research Council, US National Cancer Institute, National Institutes of Health.